Balancing Privacy and Digital Security: A Transnational Approach to International Data Protection Law: Balancing Privacy and Digital Security: A Transnational Approach to International Data Protection Law - Riko Nugraha; Yuhelson Yuhelson; Tubagus Achmad Doradjat (PENA LAW: International Journal of Law, 2026)
The growing tension between privacy rights and national security interests in the digital age points to a normative crisis in global data governance. While the European Union has adopted a rights-based approach such as the General Data Protection Regulation, many other jurisdictions have instead adopted sectoral or security-based models that widen international legal fragmentation. This article analyzes how transnational legal instruments—particularly Convention 108+, the APEC CBPR system, and OECD guidelines—can serve as a normative bridge in reconciling these differing regimes. Using a comparative-normative legal research method, this study proposes the concept of “digital precautionary principles” as a new paradigm for balancing individual privacy with legitimate security needs. The research highlights the limitations of soft law in ensuring cross-border accountability and emphasizes the importance of a principle-based harmonization approach. Conceptually, this article expands the normative framework in transnational data protection law and practically provides policy guidance for developing countries in building fair and adaptive legal infrastructure for data protection. In the midst of increasingly intensive global interconnectedness, privacy protection that does not sacrifice collective security can only be achieved through anticipatory, interoperable, and rights-based global norms.